2019
DOI: 10.1002/fsn3.820
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of γ‐glutamyltranspeptidases from dormant garlic and onion bulbs

Abstract: This study investigated the characteristics of γ‐glutamyltranspeptidases (GGTs) isolated from dormant garlic (Allium sativum L.) and onion (Allium cepa L. var. agrogatum Don) bulbs. GGTs were isolated using (NH4)2SO4 precipitation and hydrophobic interaction chromatography (phenyl‐Sepharose column). The optimal temperature, optimal pH of extraction, and the effects of metal ions and organic compounds on the activity of GGTs were investigated. The optimal pH of the GGTs of garlic and onion was 5 and 7, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Therefore, while we are able to detect significant levels of VvGGT3 transcript in the total RNA isolated from mature berry pulp, we are not able to comment on the levels of active protein in these tissues. GGTs are known to accumulate in certain storage tissues such as seed and bulbs (Balakrishna and Prabhune, 2014; Sun et al, 2019). When stored at cool temperatures below 20°C, GGT activity has been detected in the bulbs of garlic and onion.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, while we are able to detect significant levels of VvGGT3 transcript in the total RNA isolated from mature berry pulp, we are not able to comment on the levels of active protein in these tissues. GGTs are known to accumulate in certain storage tissues such as seed and bulbs (Balakrishna and Prabhune, 2014; Sun et al, 2019). When stored at cool temperatures below 20°C, GGT activity has been detected in the bulbs of garlic and onion.…”
Section: Discussionmentioning
confidence: 99%
“…It dropped below 4.2 after the rst week of aging due to carboxylic acids that formed during thermal processing by browning reaction [38]. The effect of high temperature and acidity may inhibit γ-GTP activity because the optimum pH and temperature for γ-GTP activity are pH 6 and 70 °C [39]. Therefore, samples treated with high temperatures (80 °C) have less SAC content than at low temperatures.…”
Section: Principal Component Analysis Of Black Garlic Qualities During Heat Treatmentmentioning
confidence: 99%
“…GGT activity in AGE is detectable even after 300 days, although its activity is weak (10). Sun et al reported that GGT activity derived from garlic was significantly enhanced by glucose (Glc), aspartic acid (Asp) and cysteine (Cys) (15). Saccharides in raw garlic are mainly fructans that are composed of 1-2 glycosyl linkage polymer of fructose (Fru) with the reduction end of Glc (Fig.…”
Section: S-alk(en)ylcysteinesmentioning
confidence: 99%